The Stakes of the Algerian Economy within the BRICS Group: A prospective study of BRICSA - KHELOUFI Soufyane (Journal of North African Economies, 2025)
This study aims to analyze the potential benefits and challenges of Algeria's participation within the BRICS group, comprising Brazil, Russia, India, China, and South Africa. By examining the economic dynamics, trade patterns, and investment opportunities, this study provides a prospective analysis of the stakes faced by the Algerian economy within the BRICSA framework. The findings suggest that Algeria's integration into BRICS presents significant opportunities for economic growth, increased foreign direct investment, and enhanced trade diversification. Additionally, Algeria can benefit from knowledge-sharing, technological advancements, and infrastructural development through collaboration with BRICS nations. However, challenges related to political alignment, institutional reforms, and market competitiveness may impede Algeria's full participation within the group. The study's findings provide crucial insights for policymakers, economists, and business leaders seeking to grasp the implications of Algeria's involvement in the BRICS group and its significance for socioeconomic progress.